2017
DOI: 10.1007/s10549-017-4624-7
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency (HRD) status predicts response to standard neoadjuvant chemotherapy in patients with triple-negative or BRCA1/2 mutation-associated breast cancer

Abstract: HR deficiency status is significantly associated with response to standard neoadjuvant chemotherapy in TNBC. This observation is consistent with the mechanisms of action of doxorubicin and cyclophosphamide as DNA damaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 19 publications
0
73
0
2
Order By: Relevance
“…45 In multivariable analyses of breast cancers, HRD score was able to detect significant BRCA1/2 deficiency not captured by the any single score. 43 The predictive effects of HRD score and/or HR deficiency in early-stage TNBC have been illustrated by recent studies, [45][46][47] as shown in Table 2. But in metastatic setting, the dichotomized HRD score was not found to be associated with sensitivity to carboplatin and the reason may be that nonmutated HRD-high cancers frequently reverse the homologous repair defect in metastatic setting.…”
Section: Biomarkers Associated With Genomic Instabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…45 In multivariable analyses of breast cancers, HRD score was able to detect significant BRCA1/2 deficiency not captured by the any single score. 43 The predictive effects of HRD score and/or HR deficiency in early-stage TNBC have been illustrated by recent studies, [45][46][47] as shown in Table 2. But in metastatic setting, the dichotomized HRD score was not found to be associated with sensitivity to carboplatin and the reason may be that nonmutated HRD-high cancers frequently reverse the homologous repair defect in metastatic setting.…”
Section: Biomarkers Associated With Genomic Instabilitymentioning
confidence: 93%
“…Telli(2015) 46 Phase II Neoadjuvant HRD score, BRCA1/2 mutation status HRD score 42 and BRCA1/2 mutation GeparSixto/Von Minckwitz (2015) 66 and Denkert(2015) 61 Phase II Neoadjuvant HRD score, Stromal TILs, mRNA expression of immunoactivating factors (CXCL9, CCL5, CD8A, CD80, CXCL13, IGKC, CD21), immunosuppressive factors (IDO1, PD-1, PD-L1, CTLA4, FOXP3) HRD score 42, Increased levels of stromal TILs and all 12 immune mRNA markers Tutt(2015) 69 Phase III First line BRCA1/2 mutation status,HRD score BRCA1/2 mutation Sharma(2015) 57 Prospective Neoadjuvant Hematological toxicity Thrombocytopenia ORR: overall response rate. PFS: progression-free survival.…”
Section: Platinum Salts In Early-stage Tnbcmentioning
confidence: 99%
“…Aromatase inhibitor hormone therapy is administered only in postmenopausal women to treat ER + early and/or late stage breast cancer [22]. It acts on the aromatase enzyme that still produces estrogen hormone in fat tissue of post-menopausal women or women without active ovaries.…”
Section: Hormone Therapy or Endocrine Therapymentioning
confidence: 99%
“…This accounted for approximately 15% of all cancer deaths among women globally [1]. In 2018, the highest numbers of breast cancer cases were reported from Asia (9,11,014) followed by Europe (5,22,512), North America (2,62,347), Latin America and Caribbean (199,734), Africa (1,68,690) and Oceania (24,551) [1]. Although very common in women, breast cancer rarely occurs in men [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation